On the stability of radical septic functional equations - Guariglia, Emanuel [UNESP]; Tamilvanan, Kandhasamy (My University, 2020)
This paper deals with the approximate solution of the following functional equation [formula presented] where f is a mapping from R into a normed vector space. We show stability results of this equation in quasi-β-Banach spaces and (β, p)-Banach spaces. We also prove the nonstability of the previous functional equation in a relevant case.
Keywords: (β, p)-Banach spaces; Hyers-Ulam stability; Quasi-β-Banach spaces; Radical functional equation; Septic functional equation